La terminación anticipada parcial en los supuestos de participación delictiva múltiple - Nuñez Rodriguez, Segundo Conversion (2019)
ABSTRAC This resea rch work addresses the problem of the special process of the Anticipated Termination, but not the "classical" assumption, understood as the one in which a single accused decides to submit to negotiated justice and arrives at a harmonious agreement with the Prosecutor and the party aggrieved with respect to the punishment and civil reparation, but the assumption that is regulated under the rules of article 469 of the Code of Criminal Procedure, referred to the special criminal process of Anticipated Terminat ion with a plurality of agents. In practice, this assumption occurs when two or more people are involved in the commission of the punishable act and the problematic situation arises when one of them requests to avail himself of the Anticipated Termination. Article 469 of the Code of Criminal Procedure establishes as a general rule that in these cases the early termination will proceed if all the accused agree to submit to this special process (which will imply acceptance of charges); on the contrary, this w ould entail the impossibility of arriving at an agreement of early termination with only one of the accused, even if he accepts the charges and the legal criminal consequences that it entails. In this opportunity we seek to scientifically establish whether the normative requirement of article 469 of the CPP, applies to any case of multiple criminal participation (co authorship, concurrence of authors, etc.), or only for someone in particular. In order to fulfill this purpose, specific criminal cases process ed in the Superior Court of Justice of La Libertad were analyzed (during the period of the year 2012 to 2016), where the partial early termination was requested judicially. From the study of each of them, it was possible to verify the different legal posit ions that the judges adopted when resolving a partial Early Termination requirement. In addition, with the use of the interview guide it was possible to gather information from thirty (30) criminal prosecutors from the La Libertad fiscal district, who prov ided their technical legal assessments regarding the scope of Article 469 of the CPP, on the assumptions of multiple criminal participation that developed the doctrine and jurisprudence, and on the specific assumption of plurality of agents in which the co mmon agreement of all the accused was required. Reaching objectively establish that the requirement of article 469 ° is not justified in all cases where the plurality of agents is presented, but only in cases of co authorship, since it is the only assumpti on where the conducts of the accused are linked with each other, whose sum of individual acts results in the integrity of the typical behavior (principle of reciprocal imputation).